NIL and Higher Education: An Exploration of the Early Impact of NIL on Fundraising and Competition in Universities and Athletic Departments - Meares, Wesley; Hunter, Lance; Ginn, Martha; Hatcher, William (Journal of Intercollegiate Sport, 2024)
While there has been a large amount of discussion by the media and government officials regarding the need for rules and regulations surrounding name, image, and likeness (NIL) in college athletics, to date, there is a lack of research on the effects NIL has on higher education fundraising. Thus, this study examines NIL’s effects on university and athletic fundraising and fair competition among universities. In surveying chief financial officers and athletic department directors in Power and Non-Power universities, we aim to understand university officials’ perceptions regarding the early impact NIL is having on higher education. The survey results offer valuable guidance on the regulation of NIL to ensure it benefits both universities and student-athletes.